Revealing Environmental Discourses in Online Communities: Topic Mining for Analysis of Public Agenda - Platonov, Konstantin; Svetlov, Kirill (Journal of Environmental Accounting and Management, 2026)
Environmental discourses in modern Russia are extremely diverse and controversial in their agendas and topics they discuss. Diversity shows itself in all communication channels and platforms including social media and on-line communities in particular. Social networking sites are becoming a sig-nificant source of data presenting the current trending topics and debates related to environmental issues. In this study, we investigate data from popular Russian social networking site VKontakte to understand what types of discourses are disseminated in it. The dataset of 250490 posts published on eco-related online communities in timeframe between 1.01.2017 and 01.05.2021 was collected. In sum, 7 salient clusters representing the main discourses in eco-related agenda were identified and described. Clustering based on the doc2vec algorithm proved to be an effective method to group the communities by related topics. The diversity of eco-related discourses was apparent not only in the differences in topics but also in various goals such as mobilizing, informing, education or awareness-raising. Agendas of clusters also differed in terms of alleged content consumers such as broad audiences or professionals, activists or volunteers.